GAS DISTRIBUTION SYSTEM FOR OPTIMIZATION OF THE TECHNOLOGICAL PROCESS OF COATING IN AN UNBALANCED MAGNETRON SPUTTERING INSTALLATION (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
The paper proposes a new design solution for regulating the distribution of the working gases in the vacuum chamber of the installation (UDP -850/4) for unbalanced magnetron sputtering, which will improve the mode and quality of application of multilayer nano-coatings. Constructive documentation for manufacturing a gas distribution system has been prepared, as well as instructions for assembly to the vacuum chamber.